Penafsiran Hukum Mengenai Kewenangan Notaris Dalam Membuat Akta Pertanahan - Betarqi, Bias Bumi; Yunanto, Yunanto (Notarius, 2024)
ABSTRACTThe Notary Law (UUJN) regulates the authority of notaries, but Article 15 paragraph (2) letter (f) of the UUJN grants notaries the power to draft land deeds, which were previously regulated by Government Regulation No. 37 of 1998 for PPATs. This article examines the legal interpretation of a notary's authority to draft land-related deeds based on Article 15 paragraph (2) letter (f) of the UUJN. Using a normative approach, it is found that a notary's authority is limited to legal actions concerning land that do not involve the transfer or encumbrance of land rights. This is supported by Constitutional Court Decision No. 5/PUU-XII/2014, which clarifies the distinction between the roles of notaries and PPATs in their respective duties.Keyword: Notary Authority; Land Deed.ABSTRAKUndang-Undang Jabatan Notaris (UUJN) mengatur kewenangan notaris, namun Pasal 15 ayat (2) huruf (f) UUJN memberi kewenangan kepada notaris untuk membuat akta tanah, yang sebelumnya diatur oleh PP No. 37 Tahun 1998 untuk PPAT. Artikel ini mengkaji penafsiran hukum terkait kewenangan notaris dalam pembuatan akta di bidang pertanahan berdasarkan Pasal 15 ayat (2) huruf (f) UUJN. Dengan pendekatan normatif, ditemukan bahwa kewenangan notaris terbatas pada perbuatan hukum terkait tanah yang tidak melibatkan pengalihan atau pembebanan hak atas tanah. Hal ini diperkuat oleh Putusan MK No. 5/PUU-XII/2014 yang menegaskan perbedaan kewenangan antara notaris dan PPAT dalam menjalankan tugasnya.Kata Kunci: Kewenangan Notaris; Akta Tanah